Mineralogical characteristics of copper smelting slag affecting the synchronous flotation enrichment of copper and arsenic. Issue 6 (December 2022) - Zhai, Qilin; Liu, Runqing; Wang, Changtao; Wen, Xiaofei; Li, Jie; Xie, Zhenhui; Sun, Wei
Abstract: Synchronous enrichment of copper and arsenic has become a newly emerging and significant problem during copper smelting slag (CSS) flotation, which affects environmental safety and CSS utilization. This study on CSS and its flotation products revealed the factors that affect the flotation enrichment of copper and arsenic from a mineralogy perspective. Mineralogical characteristic studies revealed that copper existed primarily in the form of matte with excellent floatability, whereas arsenic was primarily dissolved or wrapped in glassy silicates without floatability. The second occurrence phase of copper and arsenic, copper–arsenic alloy, was closely embedded with gangue minerals, which increased the difficulty of enriching copper and arsenic. Sequential extraction and X-ray photoelectron spectroscopy analysis indicated that the floatability of copper was better than that of arsenic. Flotation tests showed that copper recovery could reach 82.79 %, whereas arsenic recovery was only 40.83 %, which further confirmed that copper and arsenic could not be enriched synchronously. Mineral phase reconstruction was proposed as a potential scheme to enhance arsenic recovery. Arsenic was released from glassy silicates and combined with a copper-bearing phase to form copper–arsenic alloy during mineral phase reconstruction, which significantly increased arsenic recovery by 39.34 % and slightly increased copper recovery. The synchronous enrichment of copper and arsenic effectively reduces the total arsenic emission during copper pyrometallurgy, thereby alleviating the pressure of environmental pollution caused by CSS flotation tailings. This work provides a scientific reference for CSS processing toward recycling and harmlessness. Graphical Abstract: ga1 Highlights: Mineralogical properties of copper smelting slag (CSS) were explored in detail. Redistribution behavior of arsenic/copper during CSS flotation was studied in depth. Valuable minerals are tightly wrapped by gangue minerals and hard to liberate. Arsenic in CSS primarily exists in the form of non-floatable glassy silicates. Arsenic in glassy silicates can be released by mineral phase reconstruction.